THE EDUCATIONAL LEGACY OF PROF. DR. TUTTY ALAWIYAH: EMPOWERING BETAWI CULTURE AND WOMEN'S ROLES IN ISLAMIC DA'WAH - Maarif, Samsul; Kohari, Khalis; Sun, Ali An; Islam, Fahmi; Adnan, Mohammad (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2025)
This article explores the educational legacy of Prof. Dr. Tutty Alawiyah, focusing on her significant contributions to empowering Betawi culture and strengthening the role of women in Islamic da’wah. Prof. Alawiyah’s unique approach integrates local Betawi cultural values with broader Islamic teachings, emphasizing the importance of preserving cultural identity amidst the challenges of globalization. Her innovative da’wah strategies, implemented both locally and internationally, have made substantial strides in advancing women’s participation in Islamic scholarship and leadership. Through her initiatives, she not only reinforced Betawi traditions but also created inclusive platforms that encouraged women’s active involvement in religious education, social activism, and political engagement. By doing so, she successfully challenged traditional gender norms and paved the way for greater recognition of women’s intellectual and spiritual roles within the Muslim community. Furthermore, her leadership in organizations such as the Indonesian Muslim Women’s Preaching Council (BKMT) and her academic as well as political achievements demonstrate her multidimensional influence in shaping the discourse on women’s empowerment. This study highlights her pioneering educational initiatives and underscores the enduring impact of her contributions on both Islamic communities and Indonesian society, particularly regarding the preservation of Betawi cultural identity and the advancement of women in the field of da’wah.